STRATEGI PELESTARIAN SITUS KAPAL TENGGELAM INDONOR DI KEPULAUAN KARIMUNJAWA - , GANES P NOVIANDRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study raised the issue of conservation Topic: strategies to maintain the integrity of the vessel and its values. Problem/Issue: 1. What is the appropriate strategy for the field condition of Indonor conservation site? Purpose of the Study: The purpose of this study is to find an appropriate conservation strategy for the field condition. The adjustment is based on the ship condition, the environment, the stakeholders, and the activity around the site. Method: The methods of this study are descriptive and narrative which use inductive reasoning. Data collection technique that been used is qualitative data. The collected data will be analyzed using an analysis tool, namely the ship physical analysis of the destroyer factors, zoning analysis, legislation-based analysis, and the institutional analysis. The result of the analysis will be synthesized to obtain the ship conservation strategy of Indonor Site. Conclusion: This study has found a data about the ship physical condition and its surroundings as well as the stakeholdersâ opinions and views about the conservation. The data were collected through a literature review, an underwater diving survey, and interviews with stakeholders. Based on qualitative analysis, this study resulted a recommendation as an Indonor site conservation plan which includes three main programs, namely: protection programs, development programs, and utilization programs that are run collaboratively among the stakeholders.